Breath Acetone as Biomarker for Lipid Oxidation and Early Ketone Detection - Amlendu Prabhakar; Ashley Quach; Di Wang; Haojiong Zhang; Mirna Terrera; David Jackemeyer; Xiaojun Xian; Francis Tsow; Nongjian Tao; Erica S Forzani (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2014)
Former ketone studies, including ketoacidosis (KAD), fasting ketosis (FK), nutritional ketosis (NK), and exercis-eaffected ketosis have brought great advances to the field of ketones. In the present work, blood, urine and breath ketone detections were evaluated systematically. We found that breath ketone (acetone) is the ketone of choice for detecting early stages of ketosis. In addition, acetone was correlated with respiratory quotient, and found to be a highly sensitive non-invasive biomarker of lipid oxidation. Furthermore, acetone was used for fast screening of ketosis or ketoacidosis in populations, and demonstrated value upon screening a population of 48 individuals, among which a type I diabetes case with early symptoms of KAD and FK case were identified.